Optical and electrical studies of transparent conductive AZO and ITO sputtered thin films for CIGS photovoltaics. Issue 9 (7th May 2014) - Mereu, R. A.; Marchionna, S.; Donne, A. Le; Ciontea, L.; Binetti, S.; Acciarri, M.
Abstract Due to the many advantages of aluminum doped zinc oxide (AZO) as an alternative to indium tin oxide (ITO), the optical and electrical properties of AZO thin films deposited on large substrates by D.C. pulsed magnetron sputtering have been investigated in view of future industrial applications. In order to evaluate the effectiveness of AZO thin films as transparent conductive oxide (TCO), their properties have been compared with those of standard ITO grown with the same technique. The effect of the thickness on the optical properties revealed higher transmittance values for AZO (T>86%) than for ITO (T>83%) films. The best resistivity values obtained for AZO were about 9.7×10–4 Ωcm versus 5.09×10–4 Ωcm measured for ITO films. Moreover, it was observed that the film resistivity is significantly influenced by the working pressure in the case of AZO films while the ITO resistivity appears almost unaffected. Finally, since both the optical and electrical properties are influenced by the film thickness, it was crucial to determine the proper AZO thickness in order to obtain the optimum of electrical and optical properties for the photovoltaic applications. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)